Crecimiento y desarrollo de Copaifera paupera “copaiba” en la plantación N° 35 del CIEFOR - Puerto Almendra, Loreto – Perú. 2021 - Tuesta Valles, Amanda Esther (2023)
The study was carried out in the plantation under canopy No. 35 of CIEFOR - Puerto Almendras, made up of the species Copaifera paupera "copaiba". The objective was to determine the increase in diameter and height, survival and quality of the plants. The average increase in diameter of the C. paupera plantation was 0.99 mm, while the average increase in height of the plantation was 100.29 cm. The Chi-square test indicates that there is a significant difference between the mean increases in diameter – height and strips (p-value= 0.00 < α= 0.05). Likewise, the plantation reached a survival rate of 85%, while mortality was 15%. The largest number of plants with GOOD quality was presented by 115 seedlings representing 67.6% plants, followed by REGULAR quality with 50 live individuals indicating 29.4%. A total of 5 plants (2.9%) were identified with BAD quality. It is necessary to continue with the evaluations in order to ensure the success of the plantation, as well as carry out similar studies with other native forest species in CIEFOR - Puerto Almendra.